The healing art of tai chi becoming one with nature - Lee, Martin 1936-; Lee, Emily; Lee, Melinda 1978-; Lee, Joyce (Joyce T.) 1968- (World Scientific, 2019)
Is tai chi a stretching exercise, deep-breathing program, martial art, dance or meditation? Yes, it's all those and more. Tai chi, like many ancient Eastern practices, does not fit strict Western categories. Tai chi together with the extraordinary self-healing method developed by Dr lee, offers relief for stress, breathing disorders, muscular ailments, chronic headaches, and a variety of modern office- and sports-related complaints, as well as for deep emotional distress. Few today are as well positioned to explain the healing powers of tai chi as Dr. Martin lee, a renowned engineering physicist and tai chi master. He and his wife, Emily, also a tai chi master, are the first Americans to have studied and lived with Yu Pen-Shih, one of China's foremost ch'i kung masters. Dr. Lee has developed a ground breaking practical program that combines Eastern and Western approaches to wellness, which he calls "physical philosophy". Its goal is to help people become "one with nature", a Buddhist term for the natural restoration of true health. The rewards of one-with-nature tai chi are inner happiness, self-control, self-realization, and self-healing. Each one of these benefits receives individual attention, complete with the 64 tai chi forms, thoroughly illustrated with photographs and diagrams. The central focus is on the flow of energy - the chi,, or "inner breathe" - that tai chi evokes through Lee's four basic instructions: Relax. Breathe. Feel the earth. Do nothing extra. Here is a valuable health, exercise, and meditation program that combines ancient spiritual insights with advanced scientific knowledge and important original discoveries